2006
DOI: 10.4049/jimmunol.177.3.1967
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cytokine/Inhibitor Profiles Reshape the Understanding of the SIRS/CARS Continuum in Sepsis and Predict Mortality

Abstract: Mortality in sepsis remains unacceptably high and attempts to modulate the inflammatory response failed to improve survival. Previous reports postulated that the sepsis-triggered immunological cascade is multimodal: initial systemic inflammatory response syndrome (SIRS; excessive pro-, but no/low anti-inflammatory plasma mediators), intermediate homeostasis with a mixed anti-inflammatory response syndrome (MARS; both pro- and anti-inflammatory mediators) and final compensatory anti-inflammatory response syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
386
4
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(431 citation statements)
references
References 63 publications
31
386
4
10
Order By: Relevance
“…An exacerbated myocardial dysfunction occurred in the transgenic, as reflected by a marked profound decrease in ejection fraction, fractional shortening, or fractional area. Myocardial dysfunction frequently accompanies severe sepsis (36), yet the distinctive feature of myocardial dysfunction does not appear to be the hypoperfusion of the heart but rather the release of circulating depressant factors, including cytokines like TNFα (37). Indeed, high levels of cytokines quantified in Fpr2/3 −/− mice could underlie organ dysfunction: There are indications that unabated circulating cytokines are predictive of early mortality in sepsis (38).…”
Section: Discussionmentioning
confidence: 99%
“…An exacerbated myocardial dysfunction occurred in the transgenic, as reflected by a marked profound decrease in ejection fraction, fractional shortening, or fractional area. Myocardial dysfunction frequently accompanies severe sepsis (36), yet the distinctive feature of myocardial dysfunction does not appear to be the hypoperfusion of the heart but rather the release of circulating depressant factors, including cytokines like TNFα (37). Indeed, high levels of cytokines quantified in Fpr2/3 −/− mice could underlie organ dysfunction: There are indications that unabated circulating cytokines are predictive of early mortality in sepsis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Secretory HMGB1 augments proinflammatory response and promotes inflammation and tissue injury (33).The level of HMGB-1, was also significantly higher in LysMNrf2 2/2 compared with LysM-Keap1 2/2 . Both mice and clinical studies have documented that the balance of proinflammatory and antiinflammatory cytokines is a better predictive marker of severity and mortality in sepsis rather than a single mediator (23,34). The analysis of proinflammatory and antiinflammatory cytokines after increasing severity of CLP in mice models showed that the higher expression of antiinflammatory cytokine, such as IL-10, restrains the proinflammatory responses and improves the survival of septic mice (23).…”
Section: Discussionmentioning
confidence: 99%
“…Both mice and clinical studies have documented that the balance of proinflammatory and antiinflammatory cytokines is a better predictive marker of severity and mortality in sepsis rather than a single mediator (23,34). The analysis of proinflammatory and antiinflammatory cytokines after increasing severity of CLP in mice models showed that the higher expression of antiinflammatory cytokine, such as IL-10, restrains the proinflammatory responses and improves the survival of septic mice (23). In this study, the ratio of antiinflammatory cytokine (IL-10 or IL-1ra) versus proinflammatory cytokine (IL-6, TNF, or MIP2) was markedly higher (greater than fivefold) in LysM-Keap1 2/2 compared with LysM-Nrf2 2/2 .…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbation of the inflammatory response can lead to the development of a systemic inflammatory response syndrome (SIRS) due to an imbalance in the production of proinflammatory cytokines (Hietbrink et al 2006). Anti-inflammatory cytokines are released to restore this imbalance but over activation leads to either a compensatory anti-inflammatory response or a mixed antagonist response (Hietbrink et al 2006;Osuchowski et al 2006). The patient's immune system is in disarray and the patient becomes very susceptible to infection which might result in septic syndrome and ultimately multiple organ dysfunction (MOD) (Hietbrink et al 2006;Osuchowski et al 2006).…”
Section: Correspondence Tomentioning
confidence: 99%